Results of ARI-0001 CART19 Cells in Patients With Chronic Lymphocytic Leukemia and Richter’s Transformation - Ortiz-Maldonado, Valentín; Frigola, Gerard; Español-Rego, Marta; Balagué, Olga; Martínez-Cibrián, Nuria; Magnano, Laura; Giné, Eva; Pascal, Mariona; Correa, Juan G.; Martínez-Roca, Alexandra; Cid, Joan; Lozano, Miquel; et al. (Frontiers in Oncology, 2022)
CART19 cells are emerging as an alternative therapy for patients with chronic lymphocytic leukaemia (CLL). Here we report the outcome of nine consecutive patients with CLL treated with ARI-0001 CART19 cells, six of them with Richter’s transformation (RT). One patient with RT never received therapy. The cytokine release syndrome rate was 87.5% (12.5% grade 3). Neurotoxicity was not observed in any patient. All patients experienced absolute B-cell aplasia, and seven (87.5%) responded to therapy. With a median follow-up of 5.6 months, two patients with RT experienced a CD19-negative relapse. In conclusion, ARI-0001 cell therapy was feasible, safe, and effective in patients with high-risk CLL or RT.